Hubungan Burnout dengan Work-Life Balance pada Dosen Wanita di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Ulya Karima (Fakultas Dakwah UIN KHAS Jember, 2022)
Burnout is defined as a manifestation of an imbalance between work demands and what must be met to carry out these demands, resulting in a decrease in personal value, as well as the dignity and worth of the individual. Zulkarnain's research on the impact of burnout on work quality shows that male workers have a higher quality of work life than female workers. The focus of the problem in this study is whether there is a relationship between burnout and work life balance in female lecturers at UIN KHAS Jember. This study aims to determine the relationship between burnout and work life balance in female lecturers at UIN KHAS Jember. This research uses correlational quantitative method with sampling based on simple random sampling technique. The population in this study amounted to 126 people so that the sample in this study was 56 female lecturers at UIN KHAS Jember. Based on the results of Pearson's correlation analysis, p = 0.000 < 0.05 which indicates that the correlation between burnout and work life balance is significant. Furthermore, from the results of the Pearson correlation, it is known that the form of the relationship is negative. This means that the higher the level of burnout, the lower the level of work life balance, and vice versa if the level of burnout is lower, the higher the level of work life balance.